The stigmatisation effect of the radical right on voters' assessment of political proposals. Issue 1 (2nd January 2023) - Bolin, Niklas; Dahlberg, Stefan; Blombäck, Sofie
Abstract: Despite the continued electoral progress of the radical right, there are reasons to believe that its full electoral potential has yet to be revealed. Previous research suggests that it suffers from a stigmatisation effect and that many voters will find its proposals less compelling compared to if they were presented by a mainstream party even for policy issues they agree upon. This study employs a unique survey design, with two experiments conducted seven years apart, on a panel of Swedish voters. The aim is to evaluate whether proposals are assessed differently dependent on who the sender is and whether the effect diminishes as the cordon sanitaire of the party weakens. The results show that proposals are less liked if the sender is the radical right. This effect persists even after a weakening of the ostracisation of the radical right as well as for different types of political issues. Supplemental data for this article can be accessed online at: https://doi.org/10.1080/01402382.2021.2019977 .